2012
DOI: 10.1186/1472-6874-12-16
|View full text |Cite
|
Sign up to set email alerts
|

A population-based study of Kurdish breast cancer in northern Iraq: Hormone receptor and HER2 status. A comparison with Arabic women and United States SEER data

Abstract: BackgroundHormone receptor (HR) and HER2 expression predict the therapeutic response and prognosis of breast cancer. In the Middle-East, breast cancer is diagnosed at a young age, and Arabic women are reported to have a low frequency of HR positive tumors. This study investigates HR and HER2 expression among Kurdish and Arabic women.MethodsDuring 2008–2010, the Sulaimaniyah Directorate of Health records identified 514 Sulaimaniyah Kurdish women, 227 Kurdish women of other Governates, and 83 Arabic women with a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
27
3

Year Published

2012
2012
2018
2018

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 37 publications
(34 citation statements)
references
References 29 publications
4
27
3
Order By: Relevance
“…This result is similar to those reported in other North African countries, Iraq, Sub-Saharan Africa, Korea, China, and Taiwan [18, 2432]. However, in Western countries and other Arab and Asian countries breast cancer occurs at an older age [26, 27, 3336]. The age at diagnosis represents an important prognostic factor since tumors diagnosed at younger ages are generally more aggressive and/or less responsive to treatment [3739].…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…This result is similar to those reported in other North African countries, Iraq, Sub-Saharan Africa, Korea, China, and Taiwan [18, 2432]. However, in Western countries and other Arab and Asian countries breast cancer occurs at an older age [26, 27, 3336]. The age at diagnosis represents an important prognostic factor since tumors diagnosed at younger ages are generally more aggressive and/or less responsive to treatment [3739].…”
Section: Discussionsupporting
confidence: 88%
“…Lobular invasive carcinoma was the second most common histological type accounting for 15.3% of all cases. This level of lobular invasive carcinoma in our study is higher compared to what has been reported in Fez (Morocco) (4%), Egypt (9%), Saudi Arabia (3%) and Iraq (3.9%) [18, 26, 36, 48]. …”
Section: Discussioncontrasting
confidence: 80%
“…In the developing world, a flattening and then a decline occur about 10–15 years after the menopause. In developed countries, the age specific incidence accelerates after the menopause, and at age 70 and above doubles that seen at 45–49 years old [3–5]. The life-style changes contributing to increased post-menopausal breast cancer are largely premenopausal and include obesity, low rates of childbirth, infrequent or no lactation, early menarche, and late menopause [2].…”
Section: Introductionmentioning
confidence: 99%
“…A recently conducted international survey confined its assessment to only bleeding and pain symptomology. 6 In addition to the physical symptoms, validated quality of life measures indicate that uterine leiomyomas impact women emotionally, including increased fears about their health along with additional considerations with regard to relationships, sexual function, body image, loss of control, and hopelessness. 7 Further, the economic impact of this disease is probably underestimated given the limited amount of information on its impact on women’s work.…”
Section: Introductionmentioning
confidence: 99%